Profitability, investment, and financing decisions and their impact on firm value in the basic industry and chemicals sector - Edwin Christian; Said Kelana Asnawi (Jurnal Ekonomi Perusahaan, 2025)
The aim of this research is to find out how profitability, investment decisions and funding decisions influence company value in Basic Industry & Chemicals sector companies listed on the Indonesia Stock Exchange from 2019 to 2021. In reality, high company value does not necessarily indicate good company performance. tall. In practice, not all companies want share prices that are too high, because they are afraid that investors will not be interested in buying them. The method used in this research is a quantitative method. The data used are manufacturing companies in the Basic Industry & Chemicals sector registered on the IDX during the 2019 - 2021 period. Based on the research results, it can be concluded that profitability and funding decisions have a positive and significant effect on company value. And Investment Decisions have a positive and insignificant effect on company value.